SPATIAL DISTRIBUTION OF ACUTE CASES OF CHAGAS DISEASE REPORTED FROM 2010 TO 2020 IN THE STATE OF AMAZONAS - dos Santos, Maria Leila Fabar; Tavares, Oberdan Henrique Moreira; Colares, Giselle Gomes; da Silva, Matheus Felipe Nascimento; Damasceno, Hibelfran Alfaia; da Silva, Cleudenir Gregório; Maciel, Luiz Henrique Gonçalves; Yakubu, Michael Nosano; Gonçalves, Rosineth de Oliveira; Maciel, Marcel Gonçalves (Arquivos de Ciências da Saúde da UNIPAR, 2023)
This study aimed to investigate the epidemiology of acute cases of Chagas disease notified in the State of Amazonas between the period from 2010 to 2020. Data were obtained from the portal of the Sistema de Informação de Agravos de Notificação- SINAN, considering the number of cases per municipality of notification. 140 cases of Acute Chagas Disease were notified, distributed in 23 of the 62 municipalities of the State of Amazonas, 82 (59%) were male individuals, with a greater predominance in the age group of 20-39 years old, having 45 (32.1%) cases. As for the race/color variable, the highest number was among brown people with 101 (72.1%) notifications. The oral route prevailed as the main form of disease transmission with 93 (66.4%) records. Infection by the oral route of T. cruzi is the most important route of transmission of CD in the State of Amazonas, the occurrence of transmission is associated in most cases with the consumption of foods such as açaí juice and has been reported frequently over the years between municipalities.